Aging and Mental Health - Constanca Paul (Frontiers Research Topics, 2017)
People are progressively ageing all over the world, and it is estimated that the number of persons aged 60 or over will more than triple by 2100. This emerging population will experience an inevitable rise in dementia, mental health problems and chronic diseases. According to GBD (2010), neuropsychiatric disorders among older adults account for 6.6% of the total disability (DALYs) for this age group, with 15% suffering from a mental disorder. Multiple social, psychological and biological factors are determinant of mental health, as well as life stressors. Among these, the lack of independence, limited mobility, chronic diseases, pain, frailty or other mental and physical problems require long-term care. Beyond this, the elderly are more prone to experience events such as bereavement, a drop in socio-economic status, disability, which leads to isolation, loss of independence, loneliness and psychological distress. Mental health problems and needs assessment by health-care professionals and older people themselves are under-recognised, and the stigma surrounding mental illness makes people reluctant to seek help. The early investigation and diagnosis of these situations are crucial, as well as prior management with an important combination of pharmacological and psychosocial interventions, in conjunction with caregivers' and families' support. The present book aims to contribute to the development of knowledge in Aging and Mental Health, taking different approaches from authors, coming from diverse scientific fields, with the final goal being the improvement of quality of life and healthy aging for this growing population.